Investigation of liquid flow interaction on wax and cut channel paper-based microfluidic analytical device (μpad) - Zamri, Nur Liyana; Mohd Salleh, Mohd Hazimin (Institution of Engineering and Technology, 2018)
Simple, user-friendly, economical and rapid sensing devices are in urgent demand for diagnostics purposes especially in resource-limited countries. Diagnostics devices fabricated from patterning paper into hydrophilic and hydrophobic regions called paper-based microfluidic analytical devices (μPADs) have been introduced. In this work, straight line handcrafted channel at dimension of 3 mm width have been constructed as an inexpensive method of fabrication for wax and cut μPADs channel. For wax channel, wax hydrophobic channel is drawn on the upper side of the paper and heated for 3 minutes on 100 °C of hotplate for the diffusion of wax into the thickness of paper. 10 different viscosities of sucrose solution ranging from 0% to 70% of solute with additional of 2 blind samples is pipetted into the wax and cut channel and left horizontally for liquid flow in a minute. The flow rate is calculated. 3 types of paper which are filter paper, chromatography paper and litmus paper have been tested. In summary, it can be concluded that more viscous liquid will slow down the flow rate of liquid travel inside the wax channel compared to the cut channel and filter paper is chosen as the materials for the fabrication of μPADs channel.